Health promotion strategies among practitioners in three settings: the role of directionality and balance - Strongin, Dana Elizabeth, author; Hallahan, Kirk, advisor; Long, Marilee, committee member; Broadfoot, Kirsten J., committee member (Colorado State University. Libraries, 2010)
Twelve in-depth interviews were conducted with health promotion practitioners in northern Colorado to examine their reliance on two-way versus one-way communication (direction) and symmetrical versus asymmetrical communication (balance) to develop public information/public relations campaigns. The study contrasted strategies used by communicators working for nonprofit, hospital, and government organizations, including their perspectives about how other practitioners strategize. Contrary to expectations, the interviews revealed that practitioners in all three venues heavily relied on two-way symmetrical strategies, although they were all users of one-way communication. When discussing their perceptions, interviewees said colleagues working for organizations like theirs shared commonalities such as barriers to choosing campaign strategies; they said practitioners in other types of organizations have different barriers but more resources. The study revealed four key implications for practitioners. First, they can use creative methods, rather than depend on funding, to implement two-way strategies. Second, they should utilize audience members to spread messages to peers. Third, they can make small changes to add more symmetrical communication. Fourth, they should consider entering into more partnerships. These findings suggest that when practitioners learn what their colleagues are doing, they can create more effective campaigns, which ultimately lead to healthier communities.